The Impact of Uterine Fibroids on African American Women’s Quality of Life. - Greenfield, Jesse R. (Tufts University. Tisch Library., 2017)
Tisch Library Undergraduate Research Award Winner, 2017. Uterine fibroids are benign tumors found inside of or on uterine muscle tissue and can be the size of a pea or grow to the size of a small soccer ball. These tumors are often a painful and distressing burden to bear (Okolo, 2008). Fibroids, or leiomyomatosis, are a public health issue as they are widespread throughout much of the American female population. Women who experience side effects do so with varying severity- often based on race, age, genetics, and behavioral factors. Although fibroids can become a large burden for any individual, that holds true most often for African American, pre-menopausal, overweight women whose mothers or sisters also have the disease (Eisinger, 2015). This paper will examine the disproportionate ways African American women acquire and experience uterine fibroids as compared to white women, and analyze the ways in which access to healthcare information as well as health behaviors typical of their built environment heightens the burden of disease for these women.